STUDY COMPARISON ON KNOWLEDGE BY PRESENCE IN THE VIEWS OF IBN SĪNĀ, SUHRAWARDĪ, AND MULLĀ ṢADRĀ - Nano Warno (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2023)
This article wants to describe the science of ḥuḍūrī according to three great philosophers from Ibn Sīnā, Suhrawardī, to Mullā Ṣadrā. Even though they both adopt ḥuḍūrī science, the three of them are different in terms of paradigm and also their implementation. This research uses general hermeneutic methods on the main books of Suhrawardī, Ibn Sīnā, and Mullā Ṣadrā as well as experts in the field. Ibn Sīnā accepted the science of ḥuḍūrī only as a science of the self because he adopted the plurality paradigm of wujūd. Suhrawardī and Mullā Ṣadrā focus more on ḥuḍūrī knowledge, not only self-knowledge but also developing other forms of wujūd. Even for Suhrawardī and Mullā Ṣadrā the only true knowledge is ḥuḍūrī knowledge. Mullā Ṣadrā with his ḥuḍūrī theory of science succeeded in building unity between epistemology and ontology because he defined science with the presence of non-material in non-material. The soul is a non-material entity still weak because it is tied to the body and must undergo substantial transformation with knowledge and charity. The source of knowledge is the non-material, active mind which bestows knowledge on the subject who has carried out catharsis and then there is unity between the two. External objects are not sources of knowledge, but stimulants. Science in general and the science of ḥuḍūrī, in particular, were also later developed further into the science of God.